Chagas disease treatment efficacy markers: experiences from a Phase III study with nifurtimox in children - Grossmann, Ulrike; Rodriguez, Maria-Luisa (Frontiers in Parasitology, 2023)
Determination of success of antitrypanosomal therapy for Chagas disease is challenging, particularly in the chronic phase of the disease, because seropositivity persists for long time after successful antitrypanosomal treatment and is known to be related to the duration of the infection with Trypanosoma cruzi. Seroconversion to negative by two or more conventional serological tests is the currently accepted measure of efficacy, and studies suggest no significant change in seropositivity if left untreated, but there is no Guidance for Industry how to establish effectiveness of drugs intended for treatment of Chagas disease. Due to the lack of validated sensitive and specific, easy-to-use markers that allow early monitoring of efficacy of antitrypanosomal treatment in an efficient manner, we used seroreduction measured by two conventional enzyme-linked immunosorbent assays in addition to the currently accepted criterion for cure, seroconversion to negative, as surrogate parameter for efficacy in a Phase 3 pediatric trial with nifurtimox. The measures for confirmation of antitrypanosomal efficacy of nifurtimox were discussed with US FDA. In this Perspective article, we present our experiences obtained from a pediatric study in Chagas disease with an established drug using a surrogate efficacy parameter in addition to the established criterion for cure.